Yes, Memorize. Issue 1 (5th December 2020) - Henik, Avishai; Bar‐Hen‐Schweiger, Moran; Milshtein, Dalit; Jamaludin, Azilawati
ABSTRACT: The endless wealth of information on the internet sharpens the question: how much and what is really important for us to remember? This issue is related to questions regarding the core processes involved in reasoning and thinking. We present mental manipulation (MM) as the core of reasoning and examine the above‐mentioned issue in light of MM's vital role in reasoning and problem‐solving. Abstract : Lay abstract: The endless wealth of information on the internet sharpens the question: how much and what is really important for us to remember? This issue is related to questions regarding the core processes involved in reasoning and thinking. We present mental manipulation (MM) as the core of reasoning and examine the above‐mentioned issue in light of MM's vital role in reasoning and problem‐solving. We suggest that reducing the importance of remembering or memorizing information, because information is available (e.g., on the internet), will not help improve understanding or learning but will constrain the ability to practice MM, which will impair understanding and learning.